The crystal stair - Fisher, Catherine (Edinburgh: Barrington Stoke, 2016)
"Life in the Settlement is not as perfect as Caz and Will had hoped - they live apart in the Boys' and Girls' Towers and rarely see each other. Searching for her father, Caz is told that he never arrived at the Settlement. But then she finds his name on a secret list of a missing Search and Rescue team that set out to investigate a mysterious signal and never came back. She can't rest until she finds out what's happened to him. Even though Will is convinced it's too dangerous. Even though it means leaving and heading back out onto the endless ice ..."--Publisher's website
Keywords: Young adult fiction